Rancang Bangun dan Uji Kinerja Alat Pengasap Ikan Nila (Oreochromis niloticus) Tipe Drum - Chandra Pranata; Sandi Asmara; Oktafri Oktafri; Warji Warji (abe.fp.unila.ac.id, 2022)
This study aims to design, manufacture, and test a drum-type tilapia smoker (Oreochromis niloticus) with smoking material in the form of coconut shell with a tool capacity of > 8 kg, which is easy to move, shorter smoking time and can save fuel as much as 50%. during the curing process. This study uses the method of design, assembly or manufacture of tools, testing the results of the design, observation, and data analysis. Tilapia smoker (Oreochromis niloticus) drum type consists of several parts, namely smoking tube, exhaust funnel and thermometer, upper and lower doors, wheels, clamp hook, tube handle, fish clamp. This smoker can make smoked tilapia in less than 4 hours with coconut shell fuel, the capacity of the tool is > 8 kg. This tool smokes fish weighing 1.441 kg and consumes fuel, namely coconut shells weighing 2.9 kg. Theoretically, this tool can save energy by 67%, compared to traditional tools and 39.1% more efficient than similar tools, namely the cabinet system.